2015
DOI: 10.1038/pr.2015.27
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia downregulates angiotensin-converting enzyme-2 in human fetal lung fibroblasts

Abstract: BACKGROUND Angiotensin (ANG) II is involved in experimental hyperoxia-induced lung fibrosis. Angiotensin-converting enzyme-2 (ACE-2) degrades ANG II and is thus protective, but is downregulated in adult human and experimental lung fibrosis. Hyperoxia is a known cause of chronic fibrotic lung disease in neonates, but the role of ACE-2 in neonatal lung fibrosis is unknown. We hypothesized that ACE-2 in human fetal lung cells might be downregulated by hyperoxic gas. METHODS Fetal human lung fibroblast IMR90 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 30 publications
1
58
1
Order By: Relevance
“…If a 24h period of normoxic recovery follows the hyperoxic exposure, ACE-2 immunoreactive protein is unchanged relative to unexposed cells; this further clarifies the work of Oarhe et al (16) which showed a reduction of ACE-2 following hyperoxic exposure alone.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…If a 24h period of normoxic recovery follows the hyperoxic exposure, ACE-2 immunoreactive protein is unchanged relative to unexposed cells; this further clarifies the work of Oarhe et al (16) which showed a reduction of ACE-2 following hyperoxic exposure alone.…”
Section: Resultssupporting
confidence: 71%
“…By densitometry (Panel B), the decrease was statistically significant (p<0.05) In Panel C, TACE/ADAM17 mRNA was also reduced by when exposure to hypoxia preceded exposure to hyperoxia, in contrast to the increase in TACE mRNA caused by hyperoxic gas alone (16). …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations